Documentation of Medicinal Plants Traditionally Used in Health Care by Poumai Tribe of Manipur, India - Vemai, Shihraveine; Dilip, Salam; Ranibala, Gurumayum; Loushambam, R. S. (International Journal of Economic Plants, 2022)
The paper deals with plants used as a traditional system of medicine by the Poumai tribe of Manipur, India. The Poumai tribe is one among the major tribes of Manipur, mostly resides in the Senapati District, Manipur. Agriculture is the main source of livelihood and also the main sector for employment although it is highly unorganized and unskilled. An ethno-medicinal investigation was conducted to understand the traditional knowledge of medicinal plants being used by the local healers of Poumai tribe, Manipur, India. Some of the medicinal plants used by the community exhibits established pharmacological activities which signify the importance of the traditional knowledge of the tribes. Besides, many other species traditionally used by the tribes assume to have pharmacological potentiality. The result documented 35 plant species belonging to 23 families were found to use for curing 22 ailments. Leaf was used in the majority of cases for medicinal preparation (20 species) followed by bark, fruit, whole plant, flower, stem, bark, seed and rhizome. Among the 35 plant species, they were mainly used to treat diabetes (6 species) followed by diarrhoea and dysentery, hypertension and gastritis (5 species each). The study thus focuses on the potentials of the ethno-botanical research and the need for the proper documentation of indigenous healthcare knowledge pertaining to the medicinal plant utilization for the greater benefit of human mankind.